Community Connections: Integrating Community-Based Field Experiences to Support Teacher Education for Diversity - Christine Beaudry (Educational Considerations, 2015)
In the United States, preservice teachers often graduate and go on to work with students whose backgrounds are different from their own and in communities in which they have limited lived experience. This holds significant implications for teacher education programs given the importance of life and educational experiences in informing teaching and learning knowledge and practices and the subsequent impact of these practices in shaping the experiences and trajectories of students’ lives.
Keywords: perspectives; education; awareness; participants; importance; experience; diversity; community; teachers